Sistem Informasi Perpustakaan Sekolah Menengah Pertama Swasta (SMPS) Persatuan Guru Republik Indonesia (PGRI) Kabupaten Pelalawan - Hasibuan, Rajimar Suhal; Oriyasmi, Fadhilah; -, Seskanita; Rosman, Edwar; Zamrizal, Tengku (Universitas PGRI Sumatera Barat, 2023)
The Library Information System specifically designed for SMPS PGRI Pelalawan Regency is a technological innovation that aims to improve efficiency and serviceability in library management. By utilizing programming languages [Php, Html, and JavaScript] and relational databases such as MySQL, this system ensures optimal security and performance. The implementation of the library information system at SMPS PGRI Pelalawan Regency is expected to be able to overcome these obstacles, increase operational efficiency, and provide a better learning experience. It is hoped that the integration of technology will not only bring changes in library information management, but also stimulate students' interest in reading and make a positive contribution to improving the quality of education at SMPS PGRI Pelalawan Regency. In designing the library application at SMPS PGRI Pelalawan Regency, the data collection methods used were observation, interviews and literature study.